An Algorithm for Prevention of Unsightly Facial Scars Considering the Newest Research Insights. Issue 11 (7th November 2022) - Feinendegen, Dominik L.; Grubnik, Alexandra; Feinendegen, Sandra Y.
Abstract : Background: Unsightly scars after facial surgery might be a worry for patients and surgeons alike. To prevent unfavorable scars after facial operations, it is inevitable for the surgeon to adhere to different principles and to follow an algorithm: patient assessment, incision planning, surgical technique, suture material, and postoperative scar management. A defined knowledge about the pathophysiology of wound healing is required. The aim of this report is to serve as a teaching purpose and to verify the well-known empirical practices in scar prevention with the corresponding explanatory research. Based on these findings, the suggestion of an appropriate algorithm for the best scar management will be elaborated. Methods: This article elucidates the basics of unsightly scar prevention and the concomitant scientific proofs in detail by reviewing the literature and newest research published in PubMed. Results: The preoperative, intraoperative, and postoperative guidelines for the achievement of acceptable facial scars will be distinguished regarding the valid state of knowledge. Special attention is drawn to the "flat incision technique" as the first surgical step. Based on the newest research, an algorithm of the important preoperative, intraoperative, and postoperative features to achieve scar improvement is presented. Conclusions: To prevent unsightly facial scars, a well-defined algorithm must be followed. In summary, three well-established, empirically proven measures are documented now by the equivalent physiological scientific proof: (1) the flat incision technique, (2) the wound closure with maximal tension reduction, and (3) the postoperative scar management with further tension reduction and more moisturizing of the scar.